The willingness to boycott among Malaysian Muslims - Abdul Talib, Asmat Nizam; Abdul Latif, Samshul Amry; Alias, Nursiha (2012)
The phenomenon of consumer boycotts has been in existence in the marketplace menacing businesses and organizations since more than a century ago (Smith & Li, 2010).Yet, the rightful and deserved attention in understanding consumer boycotts were acknowledged by academicians and researchers only within the last past decade.Consumer boycott is a form of economic as well as social threat that may threaten the brand image (Klein, Smith & John, 2004) and corporate image of a firm (Lindenmeier, Tscheulin & Drevs, 2012) on a smaller scale. But on a larger scale, consumer boycotts if not carefully dealt with, may affect the host country's economy and its image. As such, the threats and occurrences of boycott can possibly upset the efforts in attracting and retaining investments in a country. Consequently, it is suffice to state that boycott is a situation where marketers, businesses, organizations or firms would want to avoid at all cost (Klein et al, 2004). Based on previous empirical researches, there are various psychological (Klein et al, 2004; Smith & Li, 2004) and social motivations underlying a boycott; as the nature of boycott is diverse (Friedman, 1985); nonetheless, boycotts are often used widely as a "coercive marketplace tactic" (John & Klein, 2003) to achieve certain instrumental or expressive goals (Friedman, 1985).